2020
DOI: 10.1177/0731684420934868
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the optical reflectance behaviour of carbon fibre composites for low-cost inspection and orientations analysis

Abstract: This work focusses on understanding and exploiting the optical reflectance behaviour of carbon fibre reinforced polymer composites for the non-destructive determination of fibre orientation and surface defects. By taking a series of images under different lighting conditions, fibre reflections have been isolated and MATLAB image analysis has been used to calculate the fibre orientations across the surface of the composite. An average peak method has been developed and validated against manual orientation measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This study improves upon the previous fibre orientation analysis 26 by excluding any results that are calculated from 'indistinct' peaks, leading to greater confidence in the fibre orientation measurements. A peak is classified as 'indistinct' when its reflectance value lies within the standard deviation of the remaining (non-peak) reflectance values, as shown in Figure 1.…”
Section: Improved Fibre Orientation Analysismentioning
confidence: 63%
See 4 more Smart Citations
“…This study improves upon the previous fibre orientation analysis 26 by excluding any results that are calculated from 'indistinct' peaks, leading to greater confidence in the fibre orientation measurements. A peak is classified as 'indistinct' when its reflectance value lies within the standard deviation of the remaining (non-peak) reflectance values, as shown in Figure 1.…”
Section: Improved Fibre Orientation Analysismentioning
confidence: 63%
“…[23][24][25] However, previous research by the authors has demonstrated a fibre orientation measurement technique based on optical reflectance that can be performed quickly across very large surfaces at a low cost. 26 As an extension of this approach, the current work improves its reliability and applies the technique to the evaluation of flow-induced fibre alignment in panels manufactured from high flow charges, presented in Experimental testing.…”
Section: Fibre Orientation Analysismentioning
confidence: 99%
See 3 more Smart Citations